Techniki marketingowe w kampanii prezydenckiej w 2010 r. - Kędzierska, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The 2010 presidential campaign in Poland took place under particularly difficult and non-standard conditions as a result of the Smolensk catastrophe and the need for early elections. This publication is an analysis of the political marketing techniques used in the context of this campaign. The aim of the text is to identify the communication tools and strategies that played a key role in shaping public opinion and contributed to the incumbent president taking the lead at the time. A concrete analysis of the campaign makes it possible to distinguish effective electoral techniques that were important in building a political advantage.
Keywords: kampania prezydencka; techniki marketingu politycznego; katastrofa smoleńska; wybory; presidential campaign; political marketing techniques; Smolensk disaster; elections